On the pre-midnight ascent of F-layer in the June solstice during the deep solar minimum in 2008 over the Indian sector - Chakrabarty, D.; Fejer, B.G.; Gurubaran, S.; Pant, Tarun K.; Abdu, M.A.; Sekar, R. (My University, 2014)
Investigations on the variations of the virtual height (h'F) of the base of the F-layer over Thumba (8.5°N, 77°E, dip lat 0.5°N) in 2002 (high solar activity) and 2008 (very low solar activity) under quiet geomagnetic conditions show characteristic pre-midnight rise of h'F in the June solstice of 2008. Comparison of the h'F variations in 2008 over Thumba and Fortaleza (3.9°S, 38.4°W, dip lat 1.8°S), Brazil, reveals that the pre-midnight rise of h'F is significantly more over Thumba during the June solstice. Drift measurements on-board the Communication/Navigation Outage Forecasting System (C/NOFS) satellite elicit that the midnight upward drift over the Indian sector during the northern summer months of 2009 is the largest, a feature that significantly weakens in 2010. C/NOFS measurements also confirm the electro-dynamical nature of the pre-midnight h'F rise over the Indian sector in the June solstice during the low solar activity. As the equatorial F-region vertical drifts during nighttime are controlled by E-region dynamo driven by tidal wind system, systematic wind measurements at upper mesospheric heights by an MF radar (1.98 MHz) from Tirunelveli (8.7°N, 77.8°E, dip lat 0.5°S), India, during 2000–2011 are used to derive the tidal components. This reveals that the phases of both the meridional and zonal components of the diurnal tide regress while the phase of the meridional component of the semidiurnal tide significantly advances with decreasing solar activity with concomitant increases in amplitudes during the summer months. These observations suggest the possible semidiurnal tidal influence on the pre-midnight h'F rise over the Indian sector in the June solstice during low solar activity.
Keywords: Pre-midnight rise of F layer; Equatorial ionosphere; Zonal electric field; Tidal winds